Democratising Housing: The socio-spatial dialectic of social housing policies - Lopes, S. S.; Marat-Mendes, T. (AMPS - Architecture Media Politics Society, 2025)
The interplay between housing policies and socio-spatial dynamics lies at the centre of debates on urban equity and democratic access to housing. In this regard this presentation aims to explore the various socio-spatial dialectics within social housing policies implemented in Portugal over the past five decades of democratic governance, emphasizing how these interventions reflect and shape spatial configurations, social structures, and policy trends. Drawing on critical theories, particularly those informed by the Marxist, the analysis exposes the evolution and impact of these policies on the territory and highlight how housing strategies have addressed— or, at times, reinforced—social inequalities, spatial segregation, and community integration. The presentation draws on case studies from diverse contexts in the Lisbon Metropolitan Area, to illustrate the contradictions embedded in social housing initiatives. These examples reveal how the spatialization of social housing limits its transformative potential. By framing housing as a socio-spatial process, this presentation advocates for rethinking social housing policies through a democratizing lens, emphasizing the recognition of housing as a fundamental right and prioritizing the reshaping of urban systems to promote spatial justice and inclusivity. This interdisciplinary approach underscores that effective social housing requires not only technical planning but also a political commitment to social justice, mediated through policies that prioritize the welfare of communities. Ultimately, the presentation argues that understanding these interdependencies offers insights into improving housing outcomes and advancing broader societal goals such as equality, sustainability, and urban resilience.